Urbanistic code compliance checking tool based on geospatial data for building licensing - Masiero, Érico; Maselli, Luccas Zambom (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The licensing process of real estate developments is regulated by technical standards and legislations. The compliance verification against such regulations, and their reference parameters, is a complicated task. Automating this process, using computational resources, can make it more efficient. The addition of geospatial data in urban code compliance checking can incorporate new methods into territorial planning. Thus, this paper aims to develop a computational geospatial tool to assist in the city of São Carlos’ building licensing process, adopting the code compliance checking method. A GIS plugin was developed for this purpose, where, based on vectorial data, the tool performs a parameter verification based on the Municipal Master Plan reference values. This tool brings public benefits as it can reduce the licensing process time and ensure sustainability and transparency. Moreover, using geospatial data enables a plethora of new urban analyses based on the same inputs of the developed tool, evolving to new government processes models.